Asymmetric anti‐Selective Michael Reaction of Imidazole‐Modified Ketones with trans‐β‐Nitroalkenes. Issue 4 (28th November 2014) - Yang, Dongxu; Wang, Linqing; Li, Dan; Han, Fengxia; Zhao, Depeng; Wang, Rui
Abstract The successful application of imidazole‐modified ketones in asymmetric anti‐selective Michael reactions with trans‐β‐nitroalkenes is presented by employing a newly developed 3‐bromothiophene‐modified chiral diamine ligand. The corresponding conjugate adduct was submitted to further transformations with Grignard reagents to solve the problem of α‐site selectivity of simple linear ketones. Additionally, the syn‐selective product was obtained by treating the anti‐selective adduct with a simple base. In this way, the site‐specific products for both diastereomers in the asymmetric conjugate addition of simple ketones to nitroalkenes can be obtained.